Age-related differences in recommended anthropometric cut-off point validity to identify cardiovascular risk factors in ostensibly healthy women. Issue 8 (December 2014) - Subramoney, Sreevidya; Björkelund, Cecilia; Guo, Xinxin; Skoog, Ingmar; Bosaeus, Ingvar; Lissner, Lauren
Aim: To investigate validity of widely recommended anthropometric and total fat percentage cut-off points in screening for cardiovascular risk factors in women of different ages. Methods: A population-based sample of 1002 Swedish women aged 38, 50, 75 (younger, middle-aged and elderly, respectively) underwent anthropometry, health examinations and blood tests. Total fat was estimated (bioimpedance) in 670 women. Sensitivity, specificity of body mass index (BMI; ≥25 and ≥30), waist circumference (WC; ≥80 cm and ≥88 cm) and total fat percentage (TF; ≥35%) cut-off points for cardiovascular risk factors (dyslipidaemias, hypertension and hyperglycaemia) were calculated for each age. Cut-off points yielding high sensitivity together with modest specificity were considered valid. Women reporting hospital admission for cardiovascular disease were excluded. Results: The sensitivity of WC ≥80 cm for one or more risk factors was ~60% in younger and middle-aged women, and 80% in elderly women. The specificity of WC ≥80 cm for one or more risk factors was 69%, 57% and 40% at the three ages (p < .05 for age trends). WC ≥80 cm yielded ~80% sensitivity for two or more risk factors across all ages. However, specificity decreased with increasing age (p < .0001), being 33% in elderly. WC ≥88 cm provided better specificity in elderly women. BMI and TF % cut-off points were not better than WC. Conclusions: Validity of recommended anthropometric cut-off points in screening asymptomatic women varies with age. In younger and middle-age, WC ≥80 cm yielded high sensitivity and modest specificity for two or more risk factors, however, sensitivity for one or more risk factor was less than optimal. WC ≥88 cm showed better validity than WC ≥80 cm in elderly. Our results support age-specific screening cut-off points for women.